Basic Level Students’ Perceptions and Practices on Assessment - Neupane, Sudip (Journal of NELTA Gandaki, 2023)
Assessment in a classroom context is a method of evaluating students’ ability and knowledge with certain purposes. This phenomenological study shared the students’ perceptions of assessment in the EFL context and explored the preparation strategies for the examination. The information for this study was collected via in-depth interviews with six participants studying at the Basic Level (Grades 6-8) in one of the private schools of Kathmandu Valley. The findings of the study showed that the students were somewhat dissatisfied with summative assessment. They suggested a balance between summative and formative assessment. The participants favoured project assessment as it provided the learners ample opportunities to learn from each other, and their performance was measured while engaging in the project activities. This study is expected to be useful for students, teachers, teacher educators, researchers, policymakers, and ELT experts by providing perceptions, insights, and assessment practices.